The Effectiveness of Using Group Investigation Technique To Enhance Students Speaking Ability at Lakidende University - Nurwanti Nurwanti; Hasmirawati Injar Lasitiha; Ikosusilowati Ikosusilowati (Universitas Pahlawan Tuanku Tambusai, 2022)
This research conducted based on background of research problem that the students need a good technique to improve their speaking ability, focus on students of Lakidende University. The sample of this research consists of 20 students (5 males and 15 females) at the third semester at Lakidende University who enrolled in academic year 2021/2022. Pre-experimental design used this research where consisting of one class only in pretest and posttest. Statistical Package for the Social Science (SPSS, version 25.0) was used to analyze the data in this research. This research used speaking tests namely pre-test and post-test. The purpose of using these speaking products are; Fluency, Pronouncation, Accuracy, Clarity, and Performance skill. The finding of this study indicated that Group Investigation technique gives significant effect on students speaking ability. This is shown by the mean score of the students speaking ability improved from only 61 to 88 after the application Group Investigation technique. Based on the result of the Wiloxon test analysis, the negative ranks column shown a value was 0 it means that there are 2 (two) students who have decreased speaking ability based on Pretest and Posttest result score with an average value 6.00. In positive ranks column shown the value was 17 means that there are 17 (seventeen) students who improve in speaking ability based on Pretest and Posttest result score with an increased value (Mean Rank) was 10.47. Besides, for the ties column value was 1 means that there was 1 (one) similirity of the same value between Pretest and Posttest result score. Based on the estimated mean value between pre post and post test, it was also known that there was an increase in student’s speaking ability after used Group Investigation Technique. Means that, Ha was accepted and Ho was rejected.